Development of nano templates for developing semiconductor nanowires - Yau, Moi Kian. (2011)
Au nanoparticles were prepared based on thermal evaporation and annealing method. The process conditions such as Au film thickness, anealing tempeature & time and annealing equiment were evaluated on the formation of the Au particles as the nano template for synthesizing semiconductor nanowires.